Determinasi Perilaku Pengelolaan Keuangan Mahasiswa Akuntansi DIY: Literasi, Inklusi, Sikap, dan Kontrol Diri - Barbara Gunawan; Muhamad Giffri Maulana (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to analyze the influence of financial literacy, financial inclusion, financial attitudes, and self-control on the financial management behavior of accounting students in the Special Region of Yogyakarta.Method: In this study, the researcher took a sample of respondents who were active undergraduate accounting students registered at universities in the Special Region of Yogyakarta that had an Accounting Study Program accredited A or "Very Good". The number of samples in this study were 122 students. This research method uses a questionnaire, then processed and analyzed with SMART PLS version 4.Finding: The results indicate that financial literacy, financial inclusion, financial attitudes, and self-control have a positive and significant influence on students' financial management behavior.Novelty: The novelty of this research lies in its integrated examination of four key determinants financial literacy, financial inclusion, financial attitude, and self-control specifically within the context of accounting students in Yogyakarta. Unlike previous studies that often focused on general populations or different demographic groups, this study provides updated empirical evidence centered on university students with academic exposure to finance, offering new insights for developing more effective financial literacy and inclusion programs.